1986
DOI: 10.3109/07420528609066354
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Catecholamine Metabolites and Cyclic Nucleotide Production

Abstract: Circadian rhythms in noradrenergic (NE) and dopaminergic (DA) metabolites and in cyclic nucleotide production were measured in discrete regions of rat brain. A circadian rhythm was found in the concentration of the NE metabolite, 3-methoxy-4-hydroxyphenylglycol (MHPG), in the hippocampus. No MHPG rhythm was found in frontal, cingulate, parietal, piriform, insular or temporal cortex, or in hypothalamus. Circadian rhythms in the concentration of the NE metabolite, 3,4-dihydroxyphenylglycol (DHPG), occurred in oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Indeed, dopamine-related substances, metabolites and receptors exhibit daily fluctuations in their levels in different brain regions (Kafka et al, 1986). Moreover, many brain regions implicated in reward-seeking behavior also contain "peripheral" (as opposed to SCN-driven) molecular clocks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, dopamine-related substances, metabolites and receptors exhibit daily fluctuations in their levels in different brain regions (Kafka et al, 1986). Moreover, many brain regions implicated in reward-seeking behavior also contain "peripheral" (as opposed to SCN-driven) molecular clocks.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rhythmic dopaminergic neurotransmission has been described in several regions of the brain, including mesolimbic structures. For example, DA and its related metabolites and receptors exhibit daily fluctuations in their levels in different brain regions (Kafka et al 1986). In particular, dopamine metabolism exhibits a diurnal rhythm in striatal regions, related to cyclic variations in the expression of DAT, DA receptors and TH (McClung 2007).…”
Section: Dopamine In the Circadian Timing Systemmentioning
confidence: 99%
“…Photoperiod is one of the largest potential sources of variation in ecometabolomics (Beck, ; Koštál, ). Numerous studies have indicated that many metabolic pathways undergo photo‐period dependent shifts, including the amino acid (Fernstrom et al., ; Gattolin et al., ), carbohydrate (Das et al., ; Seay & Thummel, ), lipid (Turek et al., ; Seay & Thummel, ), nucleotide (Kafka et al., ; Fustin et al., ), and even xenobiotic pathways (Claudel et al., ). These shifts can be correlated with the onset and cessation of major behavioural processes, perhaps most notable for entometabolomics is the control of feeding behaviour (Seay & Thummel, ).…”
Section: Entometabolomics: a Critique Of Comparative Studiesmentioning
confidence: 99%